THE EFFECTS OF SUBSIDIES ALLOCATION ON COMPETITIVENESS OF THE AGRICULTURAL ENTERPRISES FROM THE HORTICULTURAL SECTOR OF THE REPUBLIC OF MOLDOVA - Artur GOLBAN; Alexandru GORGOS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Subsidies allocation represents an important source of financing the agricultural enterprises, being analyzed by the scientists from all over the World. The subsidy policy of the Republic of Moldova is different from the subsidy policy of the European Union, being determined by the following factors: the lack of the consistency of the subsidies policies from the Republic of Moldova and the insufficiency of the necessary financial resources in order to apply the policies like in the European Union. Strategically, at the state level, it doesn’t exist a clear subsidy policy for a longer period of time, namely the subsidies measures are not very clear defined and are changing from year to year, which creates difficulties for agricultural producers to access subsidies. In this context this scientific research has the objective to analyze the subsidies effects on competitiveness of the agricultural enterprises, to analyze the subsidies allocated in Moldova compared to neighbor countries, to reveal the measures of subsidizing the agricultural enterprises and to find out if the enterprises can achieve higher competitiveness by subsidies allocation.